A study on lecturers’ self-efficacy in using technology in the centre of foundation studies, uitm dengkil campus - Shaharudin, Rozi Hanum; Azhari, Siti Hajar Aisyah (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
It is undebatable that technology adds advantages in teaching and learning and there is a need to prepare the younger generation and encourage them for changing work, social and cultural environments. This study investigates the level of self-efficacy in technology use among the lecturers at the Centre of Foundation Studies, UiTM Dengkil Campus, Selangor and the relationship between self-efficacy in technology use and the use of technology in classroom. The study also seeks explanation for the reasons to the use of technology in classroom among the lecturers. It applies both qualitative and quantitative approach to observe lecturers’ self- efficacy in using technology in teaching. Six-Point Likert-scale questions developed from Technology Proficiency Self- Assessment Scale (TPSA) were administered amongst 51 lecturers. Collected data from the survey was then prepared for the statistical procedures using Statistical Package of Social Science (SPSS) Version 2.0. It is found that there are significant correlations between lecturers’ self-efficacy in technology use and the application of technology in the classroom (r=0.413). The finding obtained from this study concludes that increases in self- efficacy are correlated with the use of technology in classroom. This study finally concludes that there is a need for lecturers to equip themselves with the current technology advancement and to apply it in the process of teaching and learning to create a more meaningful learning environment.